Intolerance of Marriage Relations between Husband and Wife (Psychological Case Study of Marital Rape) - Dewi Ulfah Arini (East Asian Journal of Multidisciplinary Research, 2023)
A harmonious marriage is based on the feeling of death, love, and appreciation between the husband and wife. A positive understanding of marital relationships makes household life harmonious by understanding the rights and obligations. Otherwise, if not the reward of rights and obligations will lead to compulsion and threats, and rape in the relationship of husband and wife. Women are thus harmed and victims and have an impact on long and short-term trauma. This study explains the psychological effects that occur due to low self-esteem, worthless and fluctuating emotions, and physical trauma. The method is done with a psychological examination to what extent and as deep as psychic victims of marital rape are interrupted and stages of intervention are performed according to the severity of the weight of the trauma. In conclusion, Marital Rape's husband is a strong driver of a woman experiencing social, psychological, and severe disorders. Advice needs guidance in advance before marriage regarding the rights and obligations of couples and the opening of a counseling center for couples without the burden of shame or pressure from the husband.